Effect of preoperative intensive statin on the efficacy and inflammatory response of acute ST-segment elevation myocardial infarction after emergency percutaneous coronary intervention: Acute STEMI after emergency percutaneous coronary intervention - Yan, Xianliang; Wang, Qian; Gao, Yulong; Yin, Chengqian (Cellular and Molecular Biology, 2023)
It was to explore the application value of individualized nursing oriented by solution-focused nursing mode in postoperative nursing of patients with pelvic fractures. 90 patients with ST-segment elevation myocardial infarction (STEMI) undergoing emergency percutaneous coronary intervention (PCI) were enrolled. They were randomly grouped into a control group and an experimental group, with 45 cases in each group. Patients in the general group were treated with conventional treatment, and patients in the enhancement group were treated with high-dose rosuvastatin based on conventional treatment. The experimental group was compared for indicators such as serum inflammatory factors, cardiac function, overall efficacy, and follow-up prognosis before and after the operation. After treatment, the total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) in the enhancement group were better as against the control group (P<0.05). Through treatment, the concentration of high-sensitivity C-reactive protein (hs-CRP), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) in the enhancement group was lower compared to the general group. The total effective rate of the enhancement group (95.56%) was higher relative to the general group (86.67%) (P<0.05). In patients with STEMI, preoperative intensive statin therapy can improve the efficacy of PCI, and reduce the inflammatory response and the incidence of cardiovascular events.